2009
DOI: 10.1007/s11010-009-0157-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical profile of Indian patients of idiopathic restrictive cardiomyopathy with and without hypertrophy

Abstract: Both idiopathic restrictive cardiomyopathy (IRCM) and hypertrophic cardiomyopathy (HCM) are part of the same disease spectrum and are due to sarcomeric gene mutations. A patient with restrictive physiology without left ventricular hypertrophy (LVH) would be diagnosed as IRCM, while one with LVH would be diagnosed as HCM with restrictive physiology. We studied a group of patients with restrictive physiology for mutations in beta-myosin heavy chain (MYH7) and troponin I (TNNI3) gene. Consecutive probands in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 12 publications
0
34
0
1
Order By: Relevance
“…However, for inherited restrictive cardiomyopathies, several recent studies demonstrate that specific sarcomeric protein mutations are associated with defects in myocardial function and increased myofilament calcium sensitivity. 162 Mutations involving cardiac troponin I (cTnI), [163][164][165][166][167] cardiac troponin T, [165][166][167][168][169] desmin, 170 -174 and ␣-␤-crystallin 175 have been most often associated with a restrictive cardiomyopathy phenotype, although alternative mutations of these proteins can also produce a hypertrophic cardiomyopathy phenotype. 166,176,177 The histological abnormalities observed in restrictive cardiomyopathies vary with, and are often diagnostic of, the underlying etiology.…”
Section: Causes and Associated Featuresmentioning
confidence: 99%
“…However, for inherited restrictive cardiomyopathies, several recent studies demonstrate that specific sarcomeric protein mutations are associated with defects in myocardial function and increased myofilament calcium sensitivity. 162 Mutations involving cardiac troponin I (cTnI), [163][164][165][166][167] cardiac troponin T, [165][166][167][168][169] desmin, 170 -174 and ␣-␤-crystallin 175 have been most often associated with a restrictive cardiomyopathy phenotype, although alternative mutations of these proteins can also produce a hypertrophic cardiomyopathy phenotype. 166,176,177 The histological abnormalities observed in restrictive cardiomyopathies vary with, and are often diagnostic of, the underlying etiology.…”
Section: Causes and Associated Featuresmentioning
confidence: 99%
“…7 They also reported a p.Arg192His mutation in TNNI3 in a adolescent Indian girl with HCM and restrictive phenotype. Two of her first degree relatives had IRC.…”
Section: Figure 1 Microphotographs Showing Thickened Endocardium (Lementioning
confidence: 96%
“…[4][5][6][7] Also, hypertrophic cardiomyopathy (HCM) and IRC have been found to be morphologically and genetically overlapping disorders. Use of precise parameters to define and classify any disease state is important.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported in another study [54], which found signs of myocardial ischemia without signs of heart failure in 15 sudden cardiac death patients. However, two other RCM studies [55,56] observed syncope, chest pain and ST segment depression in SCD patients but did not find any histological evidence of ischemia to suggest it is the underlying cause of death [55,56]. Although myocardial ischemia may occur in RCM patients, current evidence is inconclusive as to whether it is an underlying cause of sudden cardiac death in these patients suggesting the need of further autopsy studies in SCD patients or studies on coronary microcirculation to determine the role of ischemia in RCM progression and death.…”
Section: Myocardial Ischemiamentioning
confidence: 97%